Avaliação da acurácia de testes imunocromatográficos rK39 no diagnóstico da leishmaniose visceral em pacientes coinfectados com HIV - Silva , Mauro Roberto Biá da (2014)
Background: Visceral Leishmaniasis (VL) is an anthropozoonosis caused by protozoa of the genus Leishmania, especially Leishmania (Leishmania) infantum or Leishmania (Leishmania) donovani. It is present in tropical and subtropical regions and it is considered a neglected disease. The LV diagnosis is dificult, mainly for patients co infected with HIV, because LV paients present atipical clinic forms and the sorology is not trustfull Objectives: The aim of this thesis is to evaluate the accuracy of Immunochromatographic rK39 tests in the diagnosis of Visceral Leishmaniasis in serum and saliva of HIV-co-infected patients Methods: VL suspected patients were treated at the Institute of Tropical Diseases Natan Portela - IDTNP, Teresina, Piauí, Brazil, from March 2011 to October 2012. In addition to the clinical examination, it was performed the IC rK39 test in saliva and blood and also the bone marrow aspiration for parasitological and the PCR-RFLP tests. As routine in the institution, VL suggestive patients were also investigated for HIV. Bone marrow samples were collected for Leishmania research in smear, culture and PCR. For the research of Leishmania spp. in bone marrow aspirate, the Panoptic stain was used (RANYLAB Pharmaceutical Chemistry). The analyses of the stained slides were done in an optical microscope with immersion objective, magnification of 1000x. To perform the bone marrow aspirate culture, the aspirate was cultivated in 3 mL of NNN medium (McNeal, Novy & Nicolle) and 500 μL Schneider medium at 26°C. The search for promastigotes. was performed every seven days in blade - cover slip in an optical microscope. 5 mL were collected from peripheral blood in Vaccutainer® tubes without any anticoagulant in order to obtain the serum. Sera were then aliquoted in cryoassay tubes and kept in a freezer at -70°C. Saliva was collected in 50 mL polypropylene tubes and, in order to increase the amount of saliva, the patients received a piece of Parafilm® for chewing. Saliva was aliquoted in cryoessay tubes and kept in a freezer at -70°C. Results: VL patients who possessed the IC rK39 test with positive serum showed 58.6% of positivity (n = 17) in saliva (SalPos), while all of the healthy donors (CT) (n = 20) were negative in serum and saliva. The amount of total and specific IgG in the serum of patients with VL was significantly higher than that in the CT group. The specific IgG of the SalPos group was greater than in VL patients with negative saliva (SalNeg), but it was not statistically xv significant. The amount of total or specific IgA was similar in all groups. The amount of specific IgG for Leishmania found in saliva of both the SalPos and SalNeg groups was higher than in the control group, but the group with SalPos saliva presented more specific IgG to Leishmania than the SalNeg group. Among the 86 VL patients, 33 had positive serology for HIV and five tested negative serology, however, they were carriers of the virus and were being treated, totalizing 37 infected individuals. The sensitivity of VL in PCR was of 100%, since this test was considered gold standard in this study. The other tests had sensitivity of 57.14% (n = 49) (bone marrow aspiration culture), 48.71% (n = 78) (marrow aspirate smear analysis), 55.81% (n = 86) and 56 25% (n = 85) for the IC rK39 tests in Orangelife or Kalazar Detect serum, respectively. In the case of using the parasitological test as the gold standard, the sensitivity of serological tests was greater than 82%. It is not clear if HIV infection is able to interfere in the serological tests yet. Conclusions: The rK39 IC tests, with the utilization of serum, have a low sensitivity when applied to patients co-infected with HIV and VL, and the use of saliva for VL diagnosis is limited.